Synthesis of ZnSe Nanocrystals for Solid-state Lighting Applications - Kim Chi, Tran Thi; Hien, Bui Thi Thu; Thanh, Hoang Nhu; Thien, Trinh Duc; Hai, Pham Nguyen (Communications in Physics, 2021)
We report the large-scale synthesis of highly luminescent ZnSe nanocrystals (NCs) by a simple and low-cost hydrothermal method. XRD (X-ray Diffraction) and HR-TEM (High Resolution Transmission Microscopy) characterization studies confirmed the formation of as-synthesized ZnSe NCs in cubic structure. The optical property of ZnSe NCs were tunable via controlling the Zn:Se molar precursor ratio (0.5:1–1.5:1), reaction temperature (150–200 0C), and reaction time (5–30 h). The resulting ZnSe NCs with the Zn:Se precursor ratio of 1:1, hydrothermally treated at 190 0C for 20 h exhibited the highest photoluminescence quantum yield obtained by PL spectra with the 355 nm excitation. The current–voltage (I–V) characteristics of the ZnSe NCs show its promising application in the solid-state lighting.